2019
DOI: 10.1590/0034-7167-2018-0505
|View full text |Cite
|
Sign up to set email alerts
|

Educational technology for fatigue management related to antineoplastic chemotherapy

Abstract: Objective: To construct and validate an educational technology (ET) on fatigue and nonpharmacological strategies for the management of this symptom in people with cancer undergoing outpatient antineoplastic chemotherapy. Method: This is a methodological study composed of three stages: 1) elaboration of the ET using the theoretical-methodological model of Doak, Doak and Root; 2) validation of content and appearance by seven nurses via the content validity index (CVI); and 3) a pilot test with 10 patients. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
0
11
0
2
Order By: Relevance
“…The first stage, instrument construction, took place from April to May 2020 and was guided by the Doak, Doak and Root theoretical and methodological framework (10) , which indicates certain imperative guidelines for planning the preparation of educational materials (9)(10) , namely: a) determining the target audience -although it appears to be an evident step, it can often be neglected; b) establishing learning objectives, which need to be compatible with behaviors and actions, in addition to aiming writing short sentences and avoid the use of technical terms, as it makes understanding difficult; e) having interactions that can make the orientations simpler to apprehend and be remembered; f ) testing to ensure quality (9)(10) . After this stage, the content and appearance were assessed by nurse judges, experts in the field of hemoglobinopathies, from late May to July 2020.…”
Section: Study Design Place and Periodmentioning
confidence: 99%
See 2 more Smart Citations
“…The first stage, instrument construction, took place from April to May 2020 and was guided by the Doak, Doak and Root theoretical and methodological framework (10) , which indicates certain imperative guidelines for planning the preparation of educational materials (9)(10) , namely: a) determining the target audience -although it appears to be an evident step, it can often be neglected; b) establishing learning objectives, which need to be compatible with behaviors and actions, in addition to aiming writing short sentences and avoid the use of technical terms, as it makes understanding difficult; e) having interactions that can make the orientations simpler to apprehend and be remembered; f ) testing to ensure quality (9)(10) . After this stage, the content and appearance were assessed by nurse judges, experts in the field of hemoglobinopathies, from late May to July 2020.…”
Section: Study Design Place and Periodmentioning
confidence: 99%
“…The completed instrument for the assessment was built with the Google Docs tool, adapted from Perdigão et al (9) , with initial information on the characterization of participants and items to be assessed (objectives, structure, presentation, relevance and content itself ). The judges were asked to assess the ET as to content and appearance, with the answers given by a Likert-type scale: 1) inadequate (I); 2) partially adequate (PA); 3) adequate (A); 4) totally adequate (TA).…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this limitation had been pointed out by some participating judges and also finds support in other studies of educational material validation, which in turn found similar results. 31,48,49 This suggests that this dimension of the instrument needs to be re-evaluated as to its relevance for content validation.…”
Section: Dimensions Of the Content Validation Toolmentioning
confidence: 99%
“…49 Similarly, judges have reflected on the complexity involving behavioral changes and the possible limitations of the TFMP which, in isolation, would not be able to promote change without proper individual accompaniment. 48 However, it should be noted that the protocol of this research foresees a quasiexperimental study that will have as its target public nutritionists in the process of BF in the neonatal period, corresponding to the second stage of this work, in which the effectiveness of the educational technology evaluated in this study will be investigated.…”
Section: Dimensions Of the Content Validation Toolmentioning
confidence: 99%